39-3x=7(x+2)-5

Simple and best practice solution for 39-3x=7(x+2)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39-3x=7(x+2)-5 equation:


Simplifying
39 + -3x = 7(x + 2) + -5

Reorder the terms:
39 + -3x = 7(2 + x) + -5
39 + -3x = (2 * 7 + x * 7) + -5
39 + -3x = (14 + 7x) + -5

Reorder the terms:
39 + -3x = 14 + -5 + 7x

Combine like terms: 14 + -5 = 9
39 + -3x = 9 + 7x

Solving
39 + -3x = 9 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
39 + -3x + -7x = 9 + 7x + -7x

Combine like terms: -3x + -7x = -10x
39 + -10x = 9 + 7x + -7x

Combine like terms: 7x + -7x = 0
39 + -10x = 9 + 0
39 + -10x = 9

Add '-39' to each side of the equation.
39 + -39 + -10x = 9 + -39

Combine like terms: 39 + -39 = 0
0 + -10x = 9 + -39
-10x = 9 + -39

Combine like terms: 9 + -39 = -30
-10x = -30

Divide each side by '-10'.
x = 3

Simplifying
x = 3

See similar equations:

| A-15x=0 | | y=-0.5*2 | | 6a=126 | | 1.25=2x | | X/2=18/x | | 3x-34=2(x-18) | | 2.42 = p2 | | 3(3x-3)=21 | | (X+3)-2X=35+X | | 16(x+2)-4x=4(3x+2)-9 | | 8x+66=3x+31 | | x+46=5x+10 | | 89=1x+100 | | 24-9=5x | | 3/4(x-2)=-6 | | 10.44x=26.3 | | 5x(5+4)= | | CosX=-.08092 | | 7x+41=2x+11 | | 2x-4+3x=9 | | 63=5x+23 | | -3(3x+3)-2(1-14x)=3(6+6x) | | CosX=-.089092 | | 2x+17=-3-(-7x) | | 3/4(x-9)=-62 | | p-24=43 | | 5(z-3)=17.5 | | 180=24x-.4x^2 | | x+0.5y=0 | | -3/4(1/4) | | -3/4(1/5 | | (x+6)+(2-x)=16 |

Equations solver categories